PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN GUNA MENCEGAH TERJADINYA TINDAK PIDANA DI LEMBAGA PEMASYARAKATAN KELAS II A KOTA PEKANBARU MENURUT UNDANG - UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - ', Jepriza; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Pekanbaru City Class II A Penitentiary as a sub-system of criminal justiceunder Law No. 12 of 1995 plays a role in the process of preventing criminal actsby providing guidance to inmates, conducting guardianship, and guiding inmates.So from that, the writing of this thesis formulates two problems, namely: First,what is the process of guiding inmates at the Class II A Correctional Institution inPekanbaru City? Second, what are the inhibiting factors in fostering prisoners atthe Class II A Correctional Institution in Pekanbaru City?This type of research can be classified in the type of sociological legalresearch (empirical), This research was conducted at Pekanbaru City Class II ACorrectional Institution, while the population and samples were Head of Class IIA Pekanbaru Lapas Security, Class II A Pekanbaru Class Security and ProcedureSection Head, Class II A Pekanbaru Lapas Security Officer, and Prisoners. Thedata sources used are primary data, and secondary data. Data collectiontechniques in this study were interviews, questionnaires, and literature review.From the results of the problem research there are 2 main things that canbe concluded. First, the process of fostering the prisoners in the Class II ACorrectional Institution in Pekanbaru can be said to not run optimally. This isevidenced by the limited facilities and infrastructure to support the developmentprogram, the state of Lapas that has over capacity, not all prisoners are willing totake part in the coaching program, the number of prisoners who use drugs inprisons, guards officers who are caught making illegal levies, and finally the lackof correctional officers in the field of guidance and teaching staff of thedevelopment program so that the correctional system does not work well inPekanbaru Class II A Correctional Institution. Second, efforts can be madetowards fostering inmates at Pekanbaru Class II A Correctional Institution,namely: overcoming the number of occupants who are over capacity, placingprisoners based on cases, making subtle approaches to inmates who are notwilling to take part in coaching programs, making additional efforts facilities andinfrastructures that support the coaching process, make efforts to add coachingteaching staff and security officers,